Origins of mechanical preconditioning in hierarchical nanofibrous materials. (January 2022) - Gupta, Abhishek; Griesbach, Claire; Cai, Jizhe; Weigand, Steven; Meshot, Eric R.; Thevamaran, Ramathasan
Abstract: Many structured materials exhibit softening in constitutive response for the first few loading–unloading cycles–a phenomenon known as the preconditioning effect. However, the micro and nanostructural mechanisms responsible for the preconditioning effect are not well understood. We investigate the multiscale origins of the preconditioning effect in vertically aligned carbon nanotube (VACNT) foams using synchrotron X-ray scattering and mass attenuation measurements. Because of their self-organized nanofibrous structure that spans a broad lengthscale from a few angstroms to several millimeters, the VACNT foams serve as an excellent model system for soft hierarchical materials. Their hierarchical structure also leads to superior mechanical properties that are critical for extreme engineering applications. They exhibit a softening hysteretic response in the initial few compression cycles, which then remains constant over thousands of subsequent cycles. When compressed, they deform through a sequentially progressive collective buckling of the CNTs, and have the ability to recover from large strains upon unloading. We observe that the preconditioning effects arise not only from mesoscale reorganization of nanofibers as hypothesized previously, but also permanent strain in the nanoscale structure. Our findings provide insights for engineering hierarchical fibrous materials to achieve superior sustained hysteretic energy absorption and strain recovery as well as guidance for the development of physically-motivated models. Graphical abstract: